Providing pressure inputs to multizone building models. (15th May 2016) - Herring, Steven J.; Batchelor, Simon; Bieringer, Paul E.; Lingard, Bry; Lorenzetti, David M.; Parker, Simon T.; Rodriguez, Luna; Sohn, Michael D.; Steinhoff, Dan; Wolski, Matthew
Abstract: A study to assess how the fidelity of wind pressure inputs and indoor model complexity affect the predicted air change rate for a study building is presented. The purpose of the work is to support the development of a combined indoor-outdoor hazard prediction tool, which links the CONTAM multizone building simulation tool with outdoor dispersion models. The study building, representing a large office block of a simple rectangular geometry under natural ventilation, was based on a real building used in the Joint Urban 2003 experiment. A total of 1600 indoor model flow simulations were made, driven by 100 meteorological conditions which provided a wide range of building surface pressures. These pressures were applied at four levels of resolution to four different building configurations with varying numbers of internal zones and indoor and outdoor flow paths. Analysis of the results suggests that surface pressures and flow paths across the envelope should be specified at a resolution consistent with the dimensions of the smallest volume of interest, to ensure that appropriate outputs are obtained. Highlights: Low fidelity pressure inputs lead to lower air change rate predictions and can result in key flow features being lost. Predicted air change rate is reduced by 20–25% by increasing the building complexity. High fidelity, accurate pressure inputs are required to predict internal flow directions with confidence.